“PKM PELATIHAN PERAWATAN DAN PERBAIKAN RINGAN KENDARAAN BERMOTOR DALAM IMPLEMENTASI MATA KULIAH STRATEGI DIAGNOSA UNTUK MASYARAKAT DI KELURAHAN HEWULI – KABUPATEN SIKKA” - Gusti F.X.Wara Wangge; Rikardus Dole; Romualdus Paulus Sogen; Yohanes Viva Servianus (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
This community service aims to improve the understanding and basic skills of the community in Hewuli Village, Sikka Regency, in maintaining and carrying out minor repairs to motor vehicles. This activity is part of the implementation of the Diagnostic Strategy course, which integrates theory with direct practice in the field. The training focuses on early identification of vehicle problems, periodic maintenance steps, and handling minor damage that often occurs. The methods used in this activity include interactive lectures, demonstrations, and direct practice by participants. The results of the activity show an increase in the knowledge and technical skills of the community in carrying out minor services independently. This activity is expected to encourage independence and provide added economic value to the local community through applicable technical skills.